Asian Politics in Development - Benewick, Robert; Blecher, Marc; Cook, Sarah (Taylor & Francis, 2003)
This volume adopts a multidisciplinary and comparative approach to development that brings together issues that are characteristic of the lifelong scholarship of Professor Gordon White. These include a focus on the state, civil society, welfare and globalization.